Ruqyah Practice as Islamic Medicine: A Living Qur'an Study - Hudzaifah, Ahmad Faaza (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
This research discusses the existence of the practice of retaining the function of the Qur'an beyond its capacity as a revelation, namely "Medicine". The Tauhid Therapy House Nur Hidayah Bantul Yogyakarta (RTT NH) uses certain verses of the Koran, with the aim of healing. The author limits two important issues that need to be studied. How is the practice of reciting verses from the Qur'an as a healing medium in Ruqyah practice at the Tauhid Nur Hidayah Therapy House, Bantul, Yogyakarta? And what is the meaning of reading the verses of the Qur'an in the practice of ruqyah at the Tauhid Nur Hidayah Therapy House, Bantul, Yogyakarta, based on Karl Mainhemm's theory of Sociology of Knowledge? This type of research is qualitative research with field studies using three methods, namely observation, interviews and documentation. The data was analyzed by descriptive-analytic. The results of this study, ruqyah activities carried out at RTT NH are divided into three phases. Pre Therapy, Core Therapy, and Post Therapy. The meanings obtained from the practice of ruqyah in RTT NH are objective meaning, ekspresif meaning, and documentary meaning.